Nasal and Tracheal Cytological Changes After Total Laryngectomy in Long-Term Survivors. (February 2017) - Riva, Giuseppe; Boita, Monica; Corvino, Andrea; Sensini, Matteo; Peruzzetto, Daniela; Chiusa, Luigi; Pecorari, Giancarlo; Garzaro, Massimiliano
Objective: Complete separation of upper and lower respiratory tract after total laryngectomy results in permanent effects on nasal cavities and tracheo-bronchial airways. Aim of this study is evaluating nasal and tracheal cytological alterations of mucosa in laryngectomy long-term survivors, analyzing the feasibility of scraping for cytological examination of tracheal mucosa. Methods: Twenty-five laryngectomy patients underwent symptoms' evaluation, endoscopic fiber optic examination, prick tests, and nasal and tracheal scraping for cytological exam. Twenty-five healthy subjects underwent the same assessment, except for tracheal scraping. Eleven laryngectomy patients accepted inferior turbinate biopsy for histological examination. Results: Nasal cytological analysis demonstrated mucous cell metaplasia in 20% of laryngectomized patients, but it was absent in all healthy subjects; no squamous cell metaplasia was found in both groups. In 15 patients (60%), bacteria were present, without inflammatory infiltrate. Tracheal cytological analysis demonstrated a quite high rate of squamous cell metaplasia (24%), neutrophilic infiltrate (32%), and presence of bacteria (40%). Histological examination of inferior turbinate showed submucosal stromal fibrosis in all patients and submucosal inflammatory infiltrate in 1 case (9%). Conclusion: Nasal cavities and trachea of laryngectomy patients undergo long-term cytological and histological changes of mucosa and submucosa, probably due to airflow modifications.